Self-medication practice for dental problems: a cross-sectional study among adults in Kuantan, Pahang in Peninsular Malaysia - Ismail, Azlini; Abdul Majid, Muhammad Nazmi; Mohd Haron, Muhammad Nabil; Abdul Halim, Mohd Firdaus Akbar; Mohd Ibrahim, Mohamad Shafiq; Abllah, Zurainie (Wolters Kluwer - Medknow, 2023)
Aim: To investigate the prevalence, attitude, and pattern of self-medication practice for dental problems among adults in Kuantan, the state capital of Pahang, Malaysia. Materials and Methods: This cross-sectional study was conducted among adults over 18 years of age who live in Kuantan via self-administered online- and paper-based bilingual questionnaires. Descriptive statistics and chi-square analysis were run using IBM SPSS® Version 26 software. Results: From 275 respondents, one-fifth of respondents (21.8%) practised self-medication for dental problems and most of them obtained a mean attitude score of 21.7 ± 2.5% out of 25. Most self-medicating respondents were from the age group of 18–27 years (78.3%), females (55%), singles (78.3%), resides urban area (75.0%), and students (71.7%), with a household income of <MYR 3860 (46.7%), have no dental insurance (66.7 %), and did not have any family relationship with dental personnel (90.0%). Only gender has significant association with self-medication practice, X2 (1, N = 275) = 4.916, P < 0.05. Most of self-medicating respondents gained information related to self-medication from internet (62.0%) and obtained medication from pharmacy (78.0%). The major dental problem that triggered them to self-medicate was toothache (76.0%), and the majority used paracetamol for pain relief (62.0%). Their main reason for self-medication was the perceived mildness of the dental problems (60.0%). Conclusion: Adult populations in Kuantan, Pahang have moderate prevalence (21.8%) in self-medicating practice for dental problems which was mainly caused by toothache and was primarily treated with over-the-counter pain-relief medication. They also have good attitude toward appropriate self-medication.